Analysis of Existing Localization Methods - Jaromir GAJEWSKI (Communications of International Proceedings, 2025)
The article presents an overview of modern methods for locating electromagnetic signal sources, which are used in many fields, such as autonomous navigation, robotics, logistics, security, and military operations. The basic groups of methods are presented, classified according to their operating principles: methods based on amplitude, phase, time, frequency, and methods enabling the simultaneous localization of multiple transmitters operating on the same frequency. The main theoretical assumptions and examples of technical solutions are discussed, indicating their advantages and limitations.
Keywords: localization; DOA estimation; positioning